2020
DOI: 10.3390/nano10050932
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Developing Efficient Graphene Oxide-Based ZnO Photocatalysts for Dye Photo-Oxidation

Abstract: The efficient remediation of organic dyes from wastewater is increasingly valuable in water treatment technology, largely owing to the tons of hazardous chemicals currently and constantly released into rivers and seas from various industries, including the paper, pharmaceutical, textile, and dye production industries. Using solar energy as an inexhaustible source, photocatalysis ranks among the most promising wastewater treatment techniques for eliminating persistent organic pollutants and new emerging contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(55 citation statements)
references
References 114 publications
0
52
0
3
Order By: Relevance
“…However, Figure 4 d shows bit tubular morphology in the composite material, which indicates the presence of PANI. Some flaky structures are also found, which also indicates the successful polymerization of aniline and composite formation with the GO sheet [ 43 ]. This nanocomposite formation was successful as the electrode is expected to enhance the electron transportation and collection of electrons.…”
Section: Resultsmentioning
confidence: 99%
“…However, Figure 4 d shows bit tubular morphology in the composite material, which indicates the presence of PANI. Some flaky structures are also found, which also indicates the successful polymerization of aniline and composite formation with the GO sheet [ 43 ]. This nanocomposite formation was successful as the electrode is expected to enhance the electron transportation and collection of electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Azo dyes usually degrade under the influence of UV-irradiation, especially when a photocatalytic source of metal oxide is presented. ZnO, TiO2, SnO2, and CuO are mostly used as photocatalytic oxidation sources for the degradation process [ 18 , 19 ]. Methyl red is of those azo dyes which contain one or more azo groups (–N=N–) as a chromophore group that is influenced by UV absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In such a way, in the period 2016-2020, nine excellent reviews must directly or indirectly do with ZnO-graphene composites, as described in Table 1. Therefore, only two reviews were explicitly found focused on the study of ZnO-graphene composites for benzoic [31] and dye photo-oxidation [32]. Concerning the reviews' number in the topics of ZnO-based materials and graphenebased materials applied in photocatalysis (i.e., 2010-2020), there are 265 and 230 publications, respectively (Figure 8).…”
Section: Introductionmentioning
confidence: 99%